2021
DOI: 10.3390/nano11010203
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Desulfurization of Petroleum Distillate Fractions Using Manganese Dioxide Supported on Magnetic Reduced Graphene Oxide as Catalyst

Abstract: In this study, oxidative desulfurization (ODS) of modeled and real oil samples was investigated using manganese-dioxide-supported, magnetic-reduced graphene oxide nanocomposite (MnO2/MrGO) as a catalyst in the presence of an H2O2/HCOOH oxidation system. MnO2/MrGO composite was synthesized and characterized by scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD) analyses. The optimal conditions for maximum rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…4a and S6 of the ESI †). 32 For this purpose, all XPS proles were analyzed on the S 2p orbitals of the thiophene components in the bare CON-32 and in the hybrids, and several deconvolution proles were obtained (Fig. 4 and S6, † blue, purple, green lines).…”
Section: Resultsmentioning
confidence: 99%
“…4a and S6 of the ESI †). 32 For this purpose, all XPS proles were analyzed on the S 2p orbitals of the thiophene components in the bare CON-32 and in the hybrids, and several deconvolution proles were obtained (Fig. 4 and S6, † blue, purple, green lines).…”
Section: Resultsmentioning
confidence: 99%
“…The sulfur removal of MoO 3 /Al 2 O 3 (86.13) was higher than MoO 3 /SiO 2 -Al 2 O 3 (35.63). The MO catalysts can be supported on different supports such as Al 2 O 3 , SiO 2 -Al 2 O 3 , TiO 2 , Fe 3 O 4 , Fe 3 O 4 @SiO 2 , macroporous polyacrylic cationic exchange resin D113, graphene-like hexagonal BN nanosheets, silica gel, multiwalled carbon nanotubes (MWCNTs), magnetic-reduced graphene oxide (MrGO), graphite carbon, carbon nitride (g-C 3 N 4 ), CMK-3, SBA-15, MCM-41, silicon carbide (SiC), zirconia (ZrO 2 ), HY zeolite, magnetic mesoporous silica (MMS), and so on. It is shown that the support increases the catalytic activity and accessibility of metal oxides.…”
Section: Catalytic Oxidative–extractive Desulfurizationmentioning
confidence: 99%
“…Some ILs can act as both extractant and catalyst such as [Omim]­[HSO 4 ], [BPy]­[BF 4 ], and [EimC 4 SO 3 H]­NTf 2 . Some ILs can be applied as only catalysts such as [Cn­(mim) 2 ]­Cl 2 /mFeCl 3 , [EMIM]­[NiCl 2 ], [EMIM]­[CoCl 2 ], [EMIM]­[MnCl 2 ], [PW 12 O 40 ], …”
Section: Catalytic Oxidative–extractive Desulfurizationmentioning
confidence: 99%
“…Graphene possesses unique properties, such as a 1.42 Å carbon–carbon connection interval, a 3.3 Å thickness, a large surface area, high movement ability and significant optical, mechanical, electrical and thermal properties [ 37 , 38 ]. Meanwhile, GO was produced by the oxidation of graphite, which is composed of graphene and other functional groups, such as –C=O, –OH, –COOH and –COC– [ 39 ]. The existence of oxygenated functional groups on the surface of GO has caused it to have higher capacitance than graphene despite having a smaller surface area [ 40 ].…”
Section: Graphene and Graphene Oxidementioning
confidence: 99%